Sustainable and Impactful Education: Community Development within The Fourth Industrial Revolution (4IR ) In South Africa: STEAM Evaluation - Limkani Sincuba (Noyam Journals, 2024)
South Africa, amidst the Fourth Industrial Revolution's challenges, explores sustainable education intersecting with community development. Employing a mixed-methods approach, the study scrutinized educational dynamics. A case study method selected three secondary schools, involving 105 learners were purposively selected for this study. The study was underpinned by the human capital theory. This theoretical framework highlights the importance of addressing systemic inequities and promoting social justice. A questionnaire was used as a data collection tool. Qualitative data captured community perspectives, advocating for technology integration in education. Overcoming barriers like infrastructure and digital literacy was seen as crucial. The study findings highlighted integrating STEM education into South Africa's curriculum, focusing on interdisciplinary strategies to nurture creativity, critical thinking, and problem-solving skills. STEAM courses were seen as a way which prepare students for the 4IR, fostering adaptability and future employment readiness. Lack of electricity, computers, and availability of computer training was revealed as one of the lacking factors among teachers in schools. Themes were drawn and discussed in relation to the research question. The study suggests assessing long-term impacts on community indicators like economic empowerment and health. The study concluded that police makers and curriculum designers may need to re-evaluate educational systems for STEAM. The study therefore recommended that it may be of great help if rigorous outcome evaluation measures of educational intervention would be effective in schools. Also, analyzing policy frameworks was recommended as essential for national development agendas, and bridging policy gaps